Analisis Pembelajaran PKn pada Perilaku Filantropi Siswa di SD Negeri 87 Palembang - Sepriyanti, Wulan; Dedy, Adrianus; Ayurachmawati, Puji (Indonesian Research Journal on Education, 2022)
The purpose this study is to find out Civics learning in fourth grade students of philantropy students in grade IV SD Negeri 87 Palembang is still low which can be seen from indicators, such as aswa being ordered by the teacher to clean the classroom only a few students, there are students who lend tubs to friends who bring food so that students are given food brought by their freiends, there are students who are forced to donate with the teacher’s praise. This research uses descriptive qualitative method. Data collaction techniques used are observation, interviews, questionnaires and documentation. The result of this study indicate that the philantropic behavior of fourth grade students at SD Negeri 87 Palembang is include in the good category, but there are 5 students who have low philantropic behavior. This is proven based on the results the researcher’s analysis of the philantropic behavior of students who are still low, there are 5 people, namely on the selfless help indicator there is 1 student, the geneous indicator there are 2 students and the alms indicator there are 2 students.